Los programas de televisión y su influencia en el rendimiento académico de los estudiantes de 8va año de educación básica de la sección nocturna del colegio nacional Juan Montalvo de la ciudad de Machala en el período lectivo 2012-2013. - Pastor Cango, Rosa del Cisne (2013)
Television as a medium of communication is considered important since ancient times until today for all people in its life cycle; so the stage of pre-adolescents (10-12 years) and adolescents (12-18 years), have viewing habits that are not congruent, they are not correct, or have educational content, which is why incline me to investigate this issue today has much cultural impact.